2021
DOI: 10.1016/j.ijpam.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intraventricular hemorrhage in premature infants in the central region of Saudi Arabia

Abstract: Background Intraventricular hemorrhage (IVH) is a serious complication of premature (<32 weeks) deliveries, especially in very-low-birth-weight (VLBW; <1500 g) neonates. Infants developing severe IVH are more prone to long-term developmental disabilities. Although 62%–79% of women in Saudi Arabia receive antenatal steroids, IVH incidence remains high. We analyzed the risk factors for IVH in preterm VLBW neonates in the central region of Saudi Arabia. Methods We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
(50 reference statements)
4
9
0
Order By: Relevance
“…Regarding intraventricular hemorrhage, we assessed risk factors for IVH in premature infants who were less than 32 weeks' gestation and found that antenatal steroids are among the most common factors that reduce the incidence of severe IVH. 19 However, we did not examine whether the outcome would be affected by whether the patients were Saudi or not. In this study, we found that premature Saudi infants developed IVH less frequently than non-Saudis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding intraventricular hemorrhage, we assessed risk factors for IVH in premature infants who were less than 32 weeks' gestation and found that antenatal steroids are among the most common factors that reduce the incidence of severe IVH. 19 However, we did not examine whether the outcome would be affected by whether the patients were Saudi or not. In this study, we found that premature Saudi infants developed IVH less frequently than non-Saudis.…”
Section: Discussionmentioning
confidence: 99%
“…This was also shown in previous studies as they stated that a low hematocrit was associated with severe GMH-IVH in preterm neonates. Moreover, a higher initial hematocrit decreased the incidence of premature GMH-IVH [20,3]. However, it is unclear whether a low hematocrit is considered a risk factor of GMH-IVH or it is low due to bleeding [3].…”
Section: Table 1 Analysis Of Gestational Age In Weeks Of Mild Gmh-ivh and Severe Gmh-ivh [T-test] Grade I And Ii Grade Iii And Iv P-valuementioning
confidence: 99%
“…Moreover, a higher initial hematocrit decreased the incidence of premature GMH-IVH [20,3]. However, it is unclear whether a low hematocrit is considered a risk factor of GMH-IVH or it is low due to bleeding [3].…”
Section: Table 1 Analysis Of Gestational Age In Weeks Of Mild Gmh-ivh and Severe Gmh-ivh [T-test] Grade I And Ii Grade Iii And Iv P-valuementioning
confidence: 99%
See 2 more Smart Citations